Psoriasis and staphylococcus aureus skin colonization in Moroccan patients - Elfatoiki, Fatima Zahra (Pan Afr Med J, 2016)
Psoriatic lesions are rarely complicated by recurrent infections. The aim of our study is to determine skin colonisation and nasal carriage of Staphylococcus aureus in patients with psoriasis and in healthy persons. Patients and methods: a comparative study that include 33 patients with psoriasis and 33 healthy persons. Samples were taken from lesional and non lesional psoriatic skin and from healthy skin of control group. For S. aureus nasal carriage, we used sterile cotton tipped swabs. Out of165 samples (66 skin samples and 33 nasal swabs), 26 S. Aureus strains were isolated in 26 persons, 57.69% in the control group and 42.3% in the psoriasisgroup. S. aureus skin colonization was found in one case (3%) inlesional psoriatic skin vs 9 cases (27.3%) in control skin OR=0.08 IC 95% (0.01-0.70) p=0.02 and in 12,1% in non lesional soriatic skin vs 27, 3% in control skin (p =0,13). This colonization was less important in lesional psoriatic skin (3%) than in non lesional psoriatic skin (12.1%) p= 0.20. Nasal screening identified (7/33) 21, 21% S. aureus carriers in psoriasis group and in control group. Our results are in consensus withliterature findings. They have confirmed the importance of antimicrobial peptides in Innateimmunity of human skin. These peptides are normally produced bykeratinocytes in response to inflammatory stimuli such as psoriasis. Their high expression in psoriasis skin reduces the risk of skin infection and skin colonization with S. Aureus.